Spatial and social variables in the Bronze Age Phase 4 cemetery of Ban Non Wat, Northeast Thailand. (December 2015) - Smith, Baylee A.; Davies, Tilman M.; Higham, Charles F.W.
Abstract: The twelve occupation and mortuary phases at the prehistoric site of Ban Non Wat in Northeast Thailand began with late hunter-gatherers in the early 2nd millennium BC and ended with the late Iron Age in about AD 500. There are five Bronze Age mortuary phases, dating to between 1050 and 430 BC. These began with burials of exceptional wealth, but by the fourth phase, graves were markedly poorer. The 162 burials of phase 4 appear visually to form distinct groups and in the initial publication of this site, no differences between the compositions of the mortuary offerings between the five putative groups were noted. In this paper, we first conduct exploratory statistical analyses to test for the validity of spatial patterning within the cemetery, and identify four groups of burials. This is followed by the application of multinomial logistic regression to test for significant differences between them. It is concluded that three artefact classes, ceramic vessels, bivalve shells and shell beads, distinguish between the identified groups. Each of these is evaluated to clarify the subtleties of possible social distinctions in a cemetery hitherto seen as uniform. Highlights: The spatial arrangement of Bronze Age 4 burials at Ban Non Wat is analysed. Burial clusters are observed via the use of nonparametric and graphical techniques. Logistic regression identifies differences between groups based on burial goods. Density ratio surfaces support these conclusions. Social implications of group differences are discussed.